(untitled) (Journal of Nepal Physical Society, 2017)
As of late, research on the fabrication of natural dye-sensitized solar cells has been growing tremendously, largely due to its low cost and environmentally friendly nature. We have fabricated Zinc Oxide (ZnO) based Dye-sensitized Solar Cell (DSSC) using Delonix Regia, locally known as the Gulmohar flower natural dye extract. Zinc Oxide nanostructure films were allowed to grow on Fluorine-doped Tin Oxide (FTO) substrates via hydrothermal process. The seed layer for this was prepared by the spin coating method. The ZnO film’s structure, topology, and optical properties were then studied using X-ray Diffraction (XRD), an Atomic Force Microscope (AFM) and an Ultraviolet Visible (UV-Vis) Spectrophotometer respectively. The X-ray results showed the hexagonal system structure of ZnO oriented along (101) planes. The effect of ethylene glycol on the structural property of ZnO film was also studied. The current voltage curve of DSSC showed the open circuit voltage and short circuit current of 360 mV and 80 μA respectively. Journal of Nepal Physical Society Volume 4, Issue 1, February 2017, Page: 1-6